(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Colorectal cancer (CRC) is a significant global health issue, including in Saudi Arabia, where its incidence and related mortality have shown a concerning increase over the past decade. Objectives: This research aimed to evaluate the level of knowledge and awareness regarding CRC and its screening procedures among the general population in Saudi Arabia. By identifying knowledge gaps and assessing public awareness levels, this study seeks to contribute to the development of effective public health policies to combat CRC in the country. Methods: A cross-sectional questionnaire survey design was employed, utilizing a structured questionnaire developed by the researchers. The survey targeted the general adult population aged 18 years and above in Saudi Arabia, encompassing both males and females. The survey consisted of 28 questions, evaluating knowledge levels based on a scoring system categorized as poor, moderate, or high. Results: As regard knowledge and attitude score about colorectal cancer, there were (53.2%) out of 509 respondents exhibited a poor level of knowledge about this prevalent form of cancer. Additionally, (28.3%) of the participants demonstrated a high level of knowledge. However, the moderately high percentage (18.5%) of individuals revealed a moderate level of knowledge. Additionally, (41.8%) correctly identify the recommended age of 50 years for colorectal cancer screening. Conclusion: The findings revealed that a significant proportion of respondents exhibited a poor level of knowledge about CRC, while a smaller percentage demonstrated a high level of knowledge. Furthermore, many participants were unaware of the symptoms of colon cancer. Despite the recommended age for CRC screening being 50 years, a significant proportion of participants believe screening should only occur when symptoms manifest, highlighting misconceptions that must be addressed.